Primary Malignant Vaginal Melanoma – Case Report and Review of the Literature - Kühn, F.; Dieterich, M.; Klar, E.; Gerber, B.; Prinz, C. (Geburtshilfe und Frauenheilkunde, 2012)
With fewer than 250 cases published worldwide, primary vaginal melanoma is an extremely rare malignant entity which is mostly diagnosed in advanced stages. The estimated incidence of vaginal melanoma is 0.026/100 000 women per year. The poor prognosis for advanced tumour stages and different therapies used in very limited numbers of patients require precise preoperative staging and a planned interdisciplinary therapeutic approach.
Keywords: vaginal tumour; malignant melanoma; multivisceral resection